A micro model of the determinants of youth unemployment in Canada 1951--1968 - Maphangoh, Steve Qengebe Mphankomo Majola (University of Ottawa (Canada), 1972)
Abstract not available.
Keywords: Economics, Labor.; Sociology, Public and Social Welfare.; Sociology, Demography.